FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT STRESS TERHADAP MASA PERSIAPAN PENSIUN PADA PNS DI DIREKTORAT JENDERAL KEKAYAAN INTELEKTUAL KEMENTERIAN HUKUM DAN HAM FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT STRESS TERHADAP MASA PERSIAPAN PENSIUN PADA PNS DI DIREKTORAT JENDERAL KEKAYAAN INTELEKTUAL KEMENTERIAN HUKUM DAN HAM - Mey Lys Ceryah Hutasoit; Suheti; Anike Noverliantisari (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Background: The period of preparation for retirement is a period where a person will experience the loss of a permanent job and facilities from the company, resulting in stress. The stress level of a person tends to experience decreased productivity, pain, and mental disorders. Purpose of the study: This is to analyze what factors influence the stress level of a civil servant's retirement preparation period within the Directorate General of Intellectual Property, Ministry of Law and Human Rights. Methods: This research uses a cross sectional research design. Sampling technique: using total sampling with the number of respondents 55 people. In this study, the data analysis used was the Chi Square Test (P <0.05). Results: It was found that several factors were significant to stress levels with a value of α≤ 0.05, namely economic status and social support factors with OR values ​​of 12.278 and 5.841. Meanwhile, another factor that was not significant in this study was the gender factor with a p value of 0.371. Conclusion: of the three factors studied, there are 2 factors that have a relationship with the stress level of entering retirement for civil servants, namely: economic status and social support. Suggestion: to provide understanding to civil servants to prepare for their retirement day with adequate assets so that the economy is good and getting social support that can minimize the risk of stress.